Microwave-assisted in situ transesterification of wet microalgae for the production of biodiesel: progress review. Issue 1 (April 2020) - Fazril, I; Shamsuddin, A H; Nomanbhay, S; Kusomo, F; Hanif, M; Ahmad Zamri, M F M; Akhiar, A; Ismail, M F
Abstract: Continuous efforts are done by scientists in the quest of finding sustainable alternatives for fossil fuels. Various feedstock have been carefully selected to be utilized in the production of biodiesel. Microalgae has garnered a lot of attention as early as in the 80s and is regarded as one of the most promising feedstock to displace fossil fuel. However, the utilization of microalgae as feedstock in a mass production of biodiesel comes with considerable challenges. One of the main obstacles is the high cost involved in processes such as drying and the subsequent lipid extraction of the biomass. These two energy extensive processes created a bottleneck in the biodiesel production at a large scale. As a remedy, direct or in situ transesterification of the wet microalgae biomass can be applied to entirely circumvent the two processes; hence substantially reducing the production cost. However, the presence of water in the wet microalgae biomass posed a challenge in the transesterification process. This paper covers the specific techniques of utilizing microwave irradiation during the in situ transesterification of wet microalgae biomass.